Textural changes of heterozygous tomatoes in the alcobaca loci - Boas, Eduardo Valério de Barros Vilas; Chitarra, Adimilson Bosco; Maluf, Wilson Roberto; Chitarra, Maria Isabel Fernandes (Pesquisa Agropecuaria Brasileira, 2000)
Textural changes occurred during ripening of three pairs of plurilocular tomato's hybrids, nearing isogenics, excepting the alcobaca loci, were studied. The trial was carried out in Universidade Federal de Lavras (UFLA), MG, Brazil, with a randomized complete block design. The pairs of hybrids (Stevens x Flora Dade e Stevens x TOM-559; Piedmont x Flora Dade e Piedmont x TOM-559; NC-8276 x Flora Dade e NC-8276 x TOM-559) were evaluated in four stages of ripening (breaker, pink, light-red and red), in four replications. Hybrids whose common genitor was Flora Dade corresponded to the normal genotype (+/+), whereas the alcobaca heterozygous hybrids (+/alc) were originated from the common genitor TOM-559. Texture was not affected by the alcobaca allele in the predetermined stages of ripening. On the other hand, the solubilization percentage of pectic substances as well as the activity of pectinmethilesterase and polygalacturonase were influenced by the alcobaca allele which determined its contention. Tomato ripening, (+/+) and (+/alc), was characterized by intense softening associated with an increase in polygalacturonase activity and solubilization of pectic substances.